2006
DOI: 10.1016/j.margeo.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Glacial/interglacial instabilities of the Western Boundary Under Current during the last 365 kyr from Sm/Nd ratios of the sedimentary clay-size fractions at ODP site 646 (Labrador Sea)

Abstract: We present 40 Sm-Nd isotope measurements of the clay-size (<2 µm) fractions of sediments from the Southern Greenland rise (ODP-646) that span the last 365 kyr. These data track changes in the relative supply of fine particles carried into the deep Labrador Sea by the Western Boundary Under Current (WBUC) back to the fourth glacial-interglacial cycles. Earlier studies revealed three general sources of particles to the core site: (i) Precambrian crustal material from Canada, Greenland, and/or Scandinavia (North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The difference in the isotopic composition of Npl at the two sites during the MIS 5e is relatively small (2.3‰ vs. 2.5‰ on the average at Site 1302/1303 and Site 1305, respectively). This suggests a relatively well-homogenized mesopelagic water mass throughout the inner and outer Labrador Sea, assuming that both species of foraminifers developed during MIS 5e on top of the pycnocline between surface and intermediate waters, as they did during the Holocene (e.g., de Vernal and Hillaire-Marcel, 2006). On the contrary, the differences in the δ 18 O values of Cw are very large (~3.4 ‰ vs~2.7‰ at Site 1302/ 1303 and Site 1305, respectively) demonstrating that distinct deepwater mass bathed the two sites.…”
Section: The Last Interglacial (Mis 5e) Isotope Recordsmentioning
confidence: 95%
See 3 more Smart Citations
“…The difference in the isotopic composition of Npl at the two sites during the MIS 5e is relatively small (2.3‰ vs. 2.5‰ on the average at Site 1302/1303 and Site 1305, respectively). This suggests a relatively well-homogenized mesopelagic water mass throughout the inner and outer Labrador Sea, assuming that both species of foraminifers developed during MIS 5e on top of the pycnocline between surface and intermediate waters, as they did during the Holocene (e.g., de Vernal and Hillaire-Marcel, 2006). On the contrary, the differences in the δ 18 O values of Cw are very large (~3.4 ‰ vs~2.7‰ at Site 1302/ 1303 and Site 1305, respectively) demonstrating that distinct deepwater mass bathed the two sites.…”
Section: The Last Interglacial (Mis 5e) Isotope Recordsmentioning
confidence: 95%
“…A survey of the literature, prior 1994, about the late Quaternary paleoceanography of the Labrador Sea can be found in a special issue of the Canadian Journal of Earth Sciences (cf. Hillaire-Marcel et al, 1994b) whereas more recent studies are briefly reported in Hillaire-Marcel et al (2001a-b), de Vernal and Hillaire-Marcel (2006) and Fagel and Hillaire-Marcel (2006), for example. Already drilled in 1985 (ODP Leg 105; Site 646), the Eirik Ridge area was revisited in 2004 during IODP Expedition 303 in order to retrieve fresh material for higher resolution investigations from the closely located Site 1305 (57°28.5′ N, 48°31.8′ W; water depth: 3460 m; cf.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…1). These sediments are transported to the core site in the Western Boundary Undercurrent [15][16][17] (Fig. 1 and Methods), and magnetic and geochemical properties of Holocene Eirik Drift sediments document the close coupling between GIS subglacial erosion, sediment transport and terrigenous silt deposition at MD99-2227 [16][17][18] .…”
mentioning
confidence: 99%